SKYSCRAPER-01: Tiragolumab in Combination With Atezolizumab in Previously Untreated PD-L1–High, Locally Advanced, Unresectable or Metastatic Non–Small Cell Lung Cancer - Solange Peters; Roy Herbst; Hidehito Horinouchi; Luis Paz-Ares; Melissa Johnson; Benjamin J. Solomon; Mahmut Gumus; Mustafa Erman; Igor Bondarenko; Dong-Wan Kim; Enriqueta Felip; Alessandro Morabito; et al. (Journal of Clinical Oncology, 2026)
PURPOSE Tiragolumab plus atezolizumab has shown encouraging survival outcomes in metastatic non–small cell lung cancer (NSCLC), primarily in patients with PD-L1–high tumors. We further evaluated the combination of tiragolumab plus atezolizumab in the phase III SKYSCRAPER-01 study. METHODS Patients with untreated, locally advanced unresectable/metastatic PD-L1–high (by central laboratory testing) NSCLC were randomly assigned 1:1 to receive either tiragolumab (600 mg) plus atezolizumab (1,200 mg) or placebo plus atezolizumab (1,200 mg) intravenously in 21-day cycles until disease progression, loss of clinical benefit, or unacceptable toxicity. Primary end points were investigator-assessed progression-free survival (INV-PFS) and overall survival (OS) in the primary analysis set (PD-L1–high per 22C3 assay). RESULTS Five hundred twenty-one patients were randomly assigned to either the tiragolumab plus atezolizumab group (n = 262) or the placebo plus atezolizumab group (n = 259). At the primary PFS analysis (Mar 12, 2022; median follow-up 9.9 months [IQR, 6.2-13.8]), median INV-PFS was 7.0 months (95% CI, 5.6 to 9.8) with tiragolumab plus atezolizumab and 5.6 months (95% CI, 4.4 to 7.0) with placebo plus atezolizumab (hazard ratio [HR], 0.78 [95% CI, 0.63 to 0.97]; P = .02 [nonsignificant]). At the final OS analysis (Sept 24, 2024; median follow-up 17.9 months [IQR, 6.7-39.0]), median OS was 23.1 months (95% CI, 17.7 to 28.8) with tiragolumab plus atezolizumab and 16.9 months (95% CI, 14.6 to 21.3) with placebo plus atezolizumab (HR, 0.87 [95% CI, 0.7 to 1.1]; P = .22 [nonsignificant]). Overall, 41.2% (n = 110/267) and 33.8% (n = 89/263) of patients experienced grade 3-4 adverse events with tiragolumab plus atezolizumab and placebo plus atezolizumab, respectively. Four and two treatment-related deaths occurred in each group, respectively. CONCLUSION Tiragolumab plus atezolizumab did not demonstrate a statistically significant INV-PFS or OS benefit over atezolizumab in patients with previously untreated PD-L1–high NSCLC.